INTERNSHIP REPORT IN ABSOLUTION TAX CONSULTANT FIRM ABOUT TAX AMNESTY - Christopher Tjandra; Sujoko Efferin (Perpustakaan Universitas Surabaya, 2018)
Indonesia is a developing country and thus requires a large amount of fund for its development. The mains source of funding of a country is from tax. However, a significant amount of Indonesians have not paid their tax duties despite of the law. The low quality and complicatedness of taxation bureaucracy are the two main factors that causes the disobedience. The Mister of Economy is well aware of this situation and he believes that there is a high tax potential in Indonesia. Indonesians however, fear the administration sanctions and punishments the might receive if they were to pay off the tax debts that they have put off for years. Hence, the Mister of Economy implements a reformation on taxation system policy, which is the Tax Amnesty. This report explores the procedures, requirements, scope, and mechanism of Tax Amnesty, observed from the internship done at tax consultant office called Absolution, as a junior service staff on reporting the to the Tax Amnesty. The office accepts tax services such as facilitating clients who are interested in joining tax amnesty program.